The history of value system formation in ukrainian science - Olena Bocharova (Maria Curie-Skłodowska University, Lublin, Poland, 2021)
Ukrainian society at every stage of development had a specific value system, which was reflected in philosophical thought, literature and art, moral and legal standards of Ukrainian people's life, traditions, and public opinion. Referring to the researches of Ukrainian scientists in the field of pedagogy history and education theory, the article in short form presents the history of value system formation. The author focuses on the role of the value of education. The purpose of the article is to reveal the concept of "value" from Ukrainian scientists' point of view, to present the formation history of the value system, which covers the periods of the rapid development of Ukrainian society, decline in society, and modern living.